Strategi Pengembangan Usaha Tani Bawang Putih Lokal Kabupaten Belu - Kause, Wehelmina Lodia; Istiqlaal, Suci (Analisis Kebijakan Pertanian, 2025)
Local garlic in Belu Regency, NTT plays important role in regional economic development and farmers' welfare. Determining a suitable development strategy will improve the performance of this local garlic farming. By optimizing strengths and opportunities and prioritizing weaknesses and threats, farmers can manage their farming well to achieve their welfare. The purpose of this study was to formulate a strategy for developing local garlic farming in Belu Regency. This study uses a mixed-method with data analysis of EFAS, IFAS, IE matrix, and SWOT. The results of the EFAS analysis with a score of 2.74 means that external conditions are quite good and able to use opportunities to minimize threats, IFAS with a score of 2.60 means that internal conditions are quite good and able to take advantage of strengths and minimize weaknesses, IE puts it in the position of market penetration strategy and product development. SWOT analysis show SO strategy through developing garlic production centre areas and increasing ability classes as well as cooperation within and between farmer groups. WO strategy shows urgency garlic-eating movement, market penetration by the government to stabilize prices, and improving competitiveness quality by providing labelled superior seeds. Strategy WT by indicating the need for communication and information as well as technology-based development and business scale. It is recommended to use a strategy of determining the area of production centres including location, farmers, and farmer groups implementing and marketing patterns.  Other than that it is recommended to increase economies of scale and farmer groups; development of upstream-downstream agribusiness systems; grow farmer group cooperatives; agro-industry development; empowerment of BUMDes as ATM garlic farmers.